Visitor Perceptions of the Existence of the Tebet Eco Park City Park - Suesilowati, Suesilowati; Bachtiar, Heikal; Noegraha, Rosandi Ardhi (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
Jakarta is experiencing rapid growth, leading to a reduction in green open spaces (RTH). As one of the efforts to address this issue, Tebet Eco Park (TEP) has been revitalized into an urban park that serves both ecological and social functions for the community. This study aims to analyze visitors' perceptions of TEP by examining structural and personal aspects. This research employs a mixed-methods approach, integrating both qualitative and quantitative methods. Data collection was conducted through observation, interviews with park management, and distribution of questionnaires to 60 respondents. Data analysis was performed using descriptive statistics to determine visitor perceptions based on the established aspects. The results indicate that visitors' perceptions of the structural aspect obtained an average score of 2.82, while the personal aspect received an average score of 3.13. Both aspects fall into the